Vancomycin-induced thrombocytopenia: a rare adverse effect in a patient submitted to bone graft in the jaw - Danieletto, Carolina Ferrairo [UNESP]; Ferreira, Gustavo Zanna; Farah, Gustavo Jacobucci; Cuman, Roberto Kenji Nakamura (Wiley, 2017)
Introduction: Thrombocytopenia is the reduction in the number of blood platelets, which may be caused by several different conditions such as sepsis, disseminated intravascular clotting, and large blood losses. Additionally, in rare situations, thrombocytopenia may also be induced by the use of medicaments. One of these drugs is the vancomycin, a glycopeptide presently used against serious infections involving Gram-positive bacteria such as the methicillin-resistant Staphylococcus aureus and penicillin-resistant Streptococcus. Objective: The objective of this study is to report on a case of serious vancomycin-induced thrombocytopenia in a patient infected with methicillin-resistant S. aureus after mandibular reconstruction with autogenous bone graft, and to draw attention to the importance of this clinically rare adverse effect. Conclusion: Vancomycin-induced thrombocytopenia is a rare condition, which is also a significant disorder that demands attention and the rapid identification and replacement of the antimicrobial agent.
Keywords: antibacterial; bone graft; thrombocytopenia; vancomycin